2021
DOI: 10.3390/agronomy11020351
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Water Source on the Carbon Footprint of Irrigated Agriculture: A Regional Study in South-Eastern Spain

Abstract: Curbing greenhouse gas (GHG) emissions to combat climate change is a major global challenge. Although irrigated agriculture consumes considerable energy that generates GHG emissions, the biomass produced also represents an important CO2 sink, which can counterbalance the emissions. The source of the water supply considerably influences the irrigation energy consumption and, consequently, the resulting carbon footprint. This study evaluates the potential impact on the carbon footprint of partially and fully rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The global warming potential for 1 ton of artichokes is reported at 189 kg CO 2 -eq in Sicilia [26], and 860 kgCO 2 -eq in Spain [17]. Martin-Gorriz et al [36] reported that annual GHG emissions were 12.01 tonnes CO 2 ha −1 in Southeast Spain. Solinas et al [37] estimated the carbon footprint of cardoon systems ranging from 140 to 200 kg CO 2 -eq kg ton −1 .…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The global warming potential for 1 ton of artichokes is reported at 189 kg CO 2 -eq in Sicilia [26], and 860 kgCO 2 -eq in Spain [17]. Martin-Gorriz et al [36] reported that annual GHG emissions were 12.01 tonnes CO 2 ha −1 in Southeast Spain. Solinas et al [37] estimated the carbon footprint of cardoon systems ranging from 140 to 200 kg CO 2 -eq kg ton −1 .…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The intensely irrigated horticultural and fruit crops are essential to sustain the basin's economy. The export of vegetables and fruits to EU countries can exceed 70% of the total production, so the region has become known as the orchard of Europe (Martin-Gorriz et al, 2021). The TSA enabled the socioeconomic development of southeast Spain (Morote et al, 2020).…”
Section: The Tsa Systemmentioning
confidence: 99%
“…However, the inter-basin transfer continues to experience tensions between the donor and recipient basins, with the first calling for compensation given its own drought sensitivity. Moreover, since the TSA was designed in the late 1960s, adjustments based on more recent climate change predictions are needed, keeping also in mind that an increasing reliance on desalination increases the region's carbon footprint (Martin-Gorriz et al, 2021;Morote et al, 2017).…”
Section: Box 1 Increasing Agricultural Resilience Through a Multipron...mentioning
confidence: 99%